Reaksi Pasar terhadap Ketepatwaktuan Penyampaian Laporan Keuangan - Muchamad Syafruddin (Journal of Accounting and Investment, 2006)
The primary objective of this study is to investigate whether there is market reaction to the timeliness of financial report submission. Market reaction is surrogated by the impact the firms no to submit financial report on timelines on the quality of earnings information/ERC (hypothesis 1). Secondary objectives of this study is to investigate whether there is impact degree of persistence, growth, and predictability on the quality of earnings information/ERC (hypothesis 2). The second secondary objectives of this study is to investigate whether there is impact degree of risk (β) on the quality of earnings information/ERC (hypothesis 3). The third secondary objectives of  this study is to investigate whether there is impact firm size on the quality of earnings information/ERC (hypothesis 4). To conclude all of the objectives mentioned above, in model 1, cumulative abnormal returns 1 (CAR 1) are regressed on dummy (D), unexpected earnings (MUE), multiplication of dummy (D) and unexpected earnings (MUE), multiplication of market book value (MBV) and unexpected earnings (MUE), multiplication of risk (β) and unexpected earnings (MUE), and multiplication of firm size (FZ) and unexpected earnings (MUE). Furthermore, in model 2, cumulative abnormal returns 2 (CAR 2) are regressed on dummy (D), unexpected earnings (MUE), multiplication of dummy (D) and unexpected earnings (MUE), multiplication of market book value (MBV) and unexpected earnings (MUE), multiplication of risk (β) and unexpected earnings (MUE), and multiplication of firm size (FZ) and unexpected earnings (MUE). While in model 1, cumulative abnormal returns (CAR 1) are measured using event windows, from 5 days before to 5 days after the submission of financial report [-5,+5], in model 2, cumulative abnormal returns (CAR 2) are measured using event windows, from 10 days before to 10 days after the submission of financial report [-10,+10]. Chow F-Test is also used to conclude whether there is impact the firms not to submit financial report on timelines on the quality of earnings information. This study uses the sample of 82 firm years of manufacturing firms listed on the Jakarta Stock Exchange. This study uses one observation periods, 1998 – 2001 with 82 cases. The results of this study shows that the null hypothesis 1, 2  and 3 can be rejected on both model 1 and model 2. Inversely, this study shows that the null hypothesis 4 can not be rejected on both model 1 and model 2. The Chow F-Test shows that the firms not to submit financial report on timelines impacts on the quality of earnings information